Parastomal hernia: an unsolved problem of herniology - A. V. Vlasov; A. V. Panyushkin (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. The frequency of parastomal hernias reaches 58 % and occurs with any type of stoma.The OBJECTIVE was to analyze the results of open retromuscular prosthetic repair of the abdominal wall with posterior separation of components in the treatment of parastomal hernias.METHODS AND MATERIALS. Between 2019 and 2023, 11 patients with end colostomies and parastomal hernias were operated on. The median age of patients was 72 years. There were 10 women, 1 man. According to the classification of the European Society of Herniology (2014), the distribution was as follows: type I – there were no patients, type II – 1 patient, type III – 5 patients, type IV – 5 patients. One patient had a recurrent parastomal hernia. All patients underwent open retromuscular prosthetic repair of the abdominal wall with posterior separation of components and formation of a colostomy in the same place.RESULTS. The treatment results were studied in 10 patients. There was fatal outcome in 1 patient with a type IV parastomal hernia due to infection with the development of necrotizing fasciitis and cellulitis of the abdominal wall. In one case, necrosis of the colostomy occurred, which required laparoscopic mobilization and re-formation of the colostomy. Long-term results were monitored in 9 patients over a period of 1 to 4 years. Recurrence occurred in 4 patients: 1 patient with type III parastomal hernia and 5 patients with type IV (two patients had 2 relapses). With repeated relapses, in one case, there was a pinching of the section of the small intestine in the paracolostomy openingCONCLUSION. The results of treatment of parastomal hernias in our clinic were largely disappointing. Some success can be noted only in the treatment of type III parastomal hernias.